Words in the Organon - Grühn, Monika (Homœopathic Links, 2013)
“Whatʼs in a word?” If we paraphrase Shakespeare and apply it to the words used by Hahnemann in his Organon, understanding and translating each term can make a meaningful difference. Our homeopathic philosophy and practice is based on it. In this part 3, we first focus on sonderlich and eigenheitlich, which lead to deeper insights into § 153. Then, examining the term pathognomonic clarifies when so-called pathognomonic symptoms can be used in case analysis. The article concludes by discussing the insights we have got by examining the former meaning of German words. It is about resolving some errors in logic in our homeopathic philosophy, for the sake of the health of our patients.
Keywords: Organon; Former meaning of words; Errors in logic; Success rate; Sonderlich; Distinctive; Eigenheitlich; Belonging peculiarly to; Pathognomonic; Diagnosis; § 153